Optimization of distance on the transmission of long haul WDM system / Mohd Hazim Mohamed Harith - Mohamed Harith, Mohd Hazim (2012)
This project presents the design of Wavelength Division Multiplexing (WDM) with different channel and distances. In view of the current requirement for high bandwidth and transmission speed, optical fiber is being extensively used for data transmission. As the transmission system evolves to longer distance and higher bit/ rates, this technology become more useful and widely use. Optical fiber is use as a medium for telecommunication and networking because it is flexible and can be bundled as cables. WDM system is very suitable for long distance communication. Objective of this project is to design WDM system with multiple channels for long distance application and simulated it in OptiSystem software version 7.0. The transmitter will transmit signal with multiple wavelength (channels) and multiplexer will combine all the wavelength to travel in Single Mode Fiber (SMF) for long distance. At the receiver, the optical demultiplexer separates out the WDM signal and direct them to the individual channel receiver. The signal will be analyze base on Q- factor, min BER, noise and signal power. This data is successfully collect and present in graph with different channel varies with distances. The overall of the project conclude that the signal quality will decrease when the distance increased.